Optimal BMI cutoff points in obesity screening for Chinese college students - Wang, Zheng; Wang, Jinjin; Shi, Yiqin; Fang, Qun; Tan, Qiang; Wang, Mingming; Li, Jingping (Frontiers in Psychology, 2022)
Objective: An accurate BMI classification system specific to the population is of great value in health promotion. Existing studies have shown that the BMI recommended cut-off value for adults is not suitable for college students. Thus, the current study aims to identify optimal BMI cutoff points in obesity diagnosis for Chinese college students. Methods: Anthropometric assessments were performed on 6798 college students (Male = 3408, Female = 3390) from three universities in Jiangsu, China. Exploratory factor analysis (EFA) was conducted to establish the standardized models to estimate anthropometry for male and female students. Further indices were derived from the assessments, including body mass index (BMI), relative fat mass (RFM), obesity degree percentage (OBD%), waist-to-hip ratio (WHR), waist circumference (WC), and body fat percentage (BF%). The anthropometric index with the highest correlation to the models for male and female students were selected as the gold standard for obesity diagnosis. Receiver operating characteristic (ROC) curve was applied to evaluate diagnostic value of each anthropometric index according to the area under curve (AUC). Youden index maximum points determined the optimal cutoff points with the highest accuracy in obesity diagnosis. Results: The anthropometric models for both male and female students consisted of three factors. Vervaeck index was selected as the gold standard for obesity diagnosis. By comparing AUC of the anthropometric indices, we found BMI provided the highest value in obesity diagnosis. Further analysis based on Youden index identified the optimal BMI of 23.53 kg/m2 for male and 23.41 kg/m2 for female. Compared with the universal standard recommended by World Health Organization (WHO), the adjusted BMI criteria were characterized by high sensitivity as well as specificity. Conclusions: BMI is the most appropriate anthropometric index of obesity diagnosis for Chinese college students. The optimal cutoff points were lower than the WHO reference. Evidence substantiated the adjusted BMI criteria as an effective approach to improve accuracy of obesity diagnosis for this population.